Cellulose-based hydrogel beads: Preparation and characterization - Guangjun Nie (Carbohydrate Polymer Technologies and Applications, 2021)
Biopolymer-based hydrogel beads possessing intrinsic low-toxicity, biocompatibility and biodegradability have gained widespread utility in several applications. Among the biopolymers, cellulose is one of the most abundant renewable biomaterials. Herein cellulose hydrogel beads have been prepared by dissolving cellulose in 68% ZnCl2 solution and then crosslinking the polymer chains through calcium ions. The water and ethanol washing of the beads profoundly influences the beads architecture as characterized by Fourier transform infrared spectroscopy, Raman spectroscopy, X-ray powder diffraction and Scanning electron microscopy. The total crystallinity index of the beads increases with the amount of calcium ions that is further enhanced by water washing. These beads, possessing a layer-like nanoporous structure, are capable of loading bovine serum albumin (BSA) and releasing in a sustained manner. The outcome promises a large-scale production of cellulose beads having the potential to be eco-friendly and inexpensive delivery carriers in food, pharmaceutical, medical and agriculture applications.